2020
DOI: 10.1038/s41598-020-67702-2
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture intervention of visceral hypersensitivity is involved in PAR-2-activation and CGRP-release in the spinal cord

Abstract: Electroacupuncture (EA) relieves visceral hypersensitivity (VH) with underlying inflammatory bowel diseases. However, the mechanism by which EA treats ileitis-induced VH is not clearly known. To assess the effects of EA on ileitis-induced VH and confirm whether EA attenuates VH through spinal PAR-2 activation and CGRP release, goats received an injection of 2,4,6-trinitro-benzenesulfonic-acid (TNBS) solution into the ileal wall. TNBS-injected goats were allocated into VH, Sham acupuncture (Sham-A) and EA group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…PAR-2, also known as GPR11 or F2RL1, belongs to the 7-transmembrane receptors that couple to guanosine-nucleotide-binding proteins family that are encoded by F2RL1 gene ( Kawaguchi et al, 2020 ). PAR-2 is widely expressed in mammals, especially in epidermal keratinocytes and immune cells, including neutrophils, dendritic cells, T cells, and macrophages ( Sutherland et al, 2019 ; Shah et al, 2020 ). Upon its extracellular amino terminus between arginine and serine was cleaved by protease, PAR-2 is activated and further modulate multiple biological processes such as metabolism, tumorigenesis, and inflammatory response ( Kim et al, 2020 ; Wang et al, 2020 ; Bang et al, 2021 ; Jiang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…PAR-2, also known as GPR11 or F2RL1, belongs to the 7-transmembrane receptors that couple to guanosine-nucleotide-binding proteins family that are encoded by F2RL1 gene ( Kawaguchi et al, 2020 ). PAR-2 is widely expressed in mammals, especially in epidermal keratinocytes and immune cells, including neutrophils, dendritic cells, T cells, and macrophages ( Sutherland et al, 2019 ; Shah et al, 2020 ). Upon its extracellular amino terminus between arginine and serine was cleaved by protease, PAR-2 is activated and further modulate multiple biological processes such as metabolism, tumorigenesis, and inflammatory response ( Kim et al, 2020 ; Wang et al, 2020 ; Bang et al, 2021 ; Jiang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different cytokines like tumor necrosis factor-alpha (TNF-α), interlukin-1β (IL-1β), and interlukin-6 (IL-6) and disease activity index, histopathological changes scour, and myeloperoxidase (MPO) enzyme expression increase in the inflamed intestine and have an important role in VH ( Adam et al, 2013 ; Shah et al, 2016 ; Tahir et al, 2016 ). After acupuncture treatment in the 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis or ileitis model, the level of TNF-α, IL-1β, and IL-6 and disease activity index, microscopic changes scour, and MPO level were decreased and caused to attenuate VH, and weight gain was improved ( Tian et al, 2003 ; Kim et al, 2017 ; Shah et al, 2020 ).…”
Section: Peripheral Mechanism Of Electro-acupuncture For Reducing Visceral Hypersensitivitymentioning
confidence: 99%
“…A previous study showed that protease-activated receptor-2 (PAR-2) activation in different cells like granulocytes and certain agranulocytic white blood cells could induce the release of different inflammatory mediators, i.e., chemokines and prostaglandins, which promoted the production of neurogenic mediators, i.e., substance P and calcitonin gene-related peptide (CGRP), from the enteric nerve plexus and afferent nerves to ultimately trigger the VH ( Cenac et al, 2003 ; Suckow and Caudle, 2009 ). Fecal supernatant of IBS patients was injected into the colon of healthy mice that resulted in higher mucosal inflammation and increased intestinal permeability, hence contributing to VH through a PAR-2 activation mechanism ( Cenac et al, 2007 ; Annaházi et al, 2009 ; Shah et al, 2020 ). The respective findings have shown that activated PAR-2 in the intestine enhances VH.…”
Section: Peripheral Mechanism Of Electro-acupuncture For Reducing Visceral Hypersensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Wan et al 11 used an ileitis‐provoked visceral hypersensitivity (VH) model to confirm the effects of electroacupuncture on VH through Janus kinase 2 (JAK2)/signal transducers and activators of the transcription 3 (STAT3) signaling pathway in the periaqueductal gray‐rostral ventromedial medulla‐SDH axis. Very recently, Shah et al 12 used TNBS‐induced ileitis goats to study VH and reported that electroacupuncture attenuates VH through down‐regulation of spinal PAR‐2 and CGRP. The persistent pancreatitis pain induced by injection of dibutyltin dichloride in the tail vein, along with 10% alcohol in drinking water, has also been investigated in rats 13 .…”
Section: Introductionmentioning
confidence: 99%